Prototyping of a tethered undersea kite to harvest energy from low velocity currents - Günzel, Leonard; Beer, Theresa; Wucherpfennig, Sjard; Boelmann, Jan (Frontiers in Marine Science, 2022)
The global energy consumption has been on the rise since the last industrial revolution and continues to be. So far the demand could be satisfied by a mixture of conventional and renewable energies. With the global effort to eliminate conventional energies to stop the anthropological climate change, the demand for reliable and predictable renewable energies is growing. Under these circumstances, more attention is drawn towards the development of non-intermittent ocean energy systems. Apart from waves, thermal and salinity gradients, currents are an abundant and reliable ocean energy source. Inspired by state-of-the-art technology, a unique system for current energy, the Current Kite, is presented in the following paper. This tethered undersea kite (TUSK) consist of a wing to which a turbine is attached. The wing drags the turbine through the water in a certain trajectory, sweeping a large area at a relative speed that is several times the actual speed of the underwater current. In the following paper we present the general setup and design of our first and second prototype. The first prototype was build as a prove of concept. It was equipped with active steering and several on board sensors. With the second prototype the aim was to build a more sophisticated system, which would make the active steering redundant and use more efficient, circular flight paths. A wing which would adjust itself in the current and follow the predefined circular path, was designed using numerical simulations. To achieve this circular flight movement without twisting the electrical cable, a swivel and a stress reducer were designed and built to connect the TUSK as well as transfer electrical power to land. In addition the tracking-system was redesigned, communicating by modulation over the power line. This provides a fully autonomous ocean current power plant, which communicates in real time data and has a promising outlook in efficiency, regarding to the state of art. Due to Covid-19 regulations it was not possible to test the prototype. Therefore the paper mainly focuses on the design and construction process, up to the production of the TUSK.